Розробка пристрою керування побутовими приладами за допомогою wi-fi - Чапарин, І. М. (ХНУРЕ, 2022)
There are many household appliances that can be controlled using an IR remote control; however, this method is no longer entirely relevant at the present time. As in the modern world the quantity of the devices is controlled with a smartphone grows, which allows, in addition to simple control, to come up with various automation scenarios. Above mentioned solution allows you to achieve this goal performing the process with the Arduino microcontroller and some additional modules for it. The proposed solution is can be called universal and offers management options via a web interface, which eliminates the need to install additional mobile applications.